Sirtuin 6 mediates the therapeutic effect of endometrial regenerative cell-derived exosomes in alleviation of acute transplant rejection by weakening c-myc-dependent glutaminolysis - Liu, Tong; Sun, Chenglu; Liu, Xu; Zhao, Pengyu; Shao, Bo; Xu, Yini; Xiao, Yiyi; Wang, Hongda; Chen, Qiang; Yang, Guangmei; Wang, Hao (Frontiers in Cell and Developmental Biology, 2025)
BackgroundDespite the rapid development of immunosuppressive drugs, acute rejection (AR) remains a cause of allograft dysfunction and allograft failure. Although endometrial regenerative cell-derived exosomes (ERC-Exos) effectively alleviate AR, more research is required to fully understand the underlying mechanisms. Thus, this study aimed to determine whether sirtuin 6 (SIRT6) mediates the therapeutic effect of ERC-Exos on AR and elucidate the underlying mechanisms.MethodsThe expression of SIRT6 was verified in ERC-Exos by Western blot. ERC-Exos with extremely low expression of SIRT6 (SIRT6-KD-ERC-Exos) were obtained by transducing shRNA-SIRT6 in ERCs. C57BL/6 recipient mice were transplanted with heart grafts from BALB/c donor mice and divided into three groups: untreated, ERC-Exo-treated, and SIRT6-KD-ERC-Exo-treated groups. Recipient mice were sacrificed on post-operative day 8 for the determination of graft pathological changes, intra-graft immunocyte infiltration, splenic CD4+ T cell populations, and serum cytokine levels in vivo. The proportion of CD4+ T cells and their secreting cytokine levels were determined in vitro. Besides, the underlying mechanisms were also investigated in vitro.ResultsERC-Exos expressed SIRT6, and cardiac graft survival was increased by SIRT6-expressing ERC-Exos. Graft pathological damage, intra-graft CD4+ T cell infiltration, and intra-graft inflammatory (Th1 and Th17) cell infiltration decreased, and intra-graft and serum inflammatory cytokine (interferon (IFN)-γ and interleukin (IL)-17) levels decreased in the SIRT6-expressing ERC-Exo-treated mice. Furthermore, in the recipient mice, ERC-Exo treatment markedly increased the differentiation of regulatory T cells (Tregs) while significantly decreasing that of Th1 and Th17 cells. In a similar vein, ERC-Exo therapy raised the levels of the anti-inflammatory cytokine IL-10 in vitro while decreasing those of IFN-γ and IL-17. By suppressing the expression of important proteins linked to glutaminolysis and further deactivating the mammalian target of rapamycin complex 1 (mTORC1) pathway, ERC-Exos reduced the uptake and use of glutamine in naïve CD4+ T cells, according to mechanism exploration. In contrast, SIRT6-KD-ERC-Exos considerably reversed these trends and changes both in vivo and in vitro.ConclusionSIRT6 is crucial in mediating ERC-Exos to remodel CD4+ T cell differentiation by weakening c-Myc-dependent glutaminolysis, thereby alleviating AR.